Cost Estimation of Distillation Unit at Dimethyl Ether Plant Based on Production Capacity - E Saputro; B A Sanjoyo; W Ramadhanti (BIOMEJ, 2022)
The aim of this research is to determine the impact of production capacity in determining of distillation cost estimation on the dimethyl ether plant design. The estimation of equipment costs are determined using the CEPCI cost index. The calculation of the equipment specification was done with 4 different production capacities. The number of column height and diameter will increase when the production capacity is increased. The increase of the equipment cost is directly proportional to the increase of production capacity. The greater the production capacity, the larger the height column and diameter, so the equipment cost will increase also. The equipment cost is affected by production capacity. Based on this analysis, the cost in the year of 2024 will follow the model of y = 9923.8x + 2E+08, which x is the capacity.